2022
DOI: 10.1007/s12640-022-00572-w
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and Dynamic Alpha-Neurotoxicity Within Venoms from the Palearctic Viperid Snake Clade of Daboia, Macrovipera, Montivipera, and Vipera

Abstract: The targeting of specific prey by snake venom toxins is a fascinating aspect of molecular and ecological evolution. Neurotoxic targeting by elapid snakes dominates the literature in this regard; however, recent studies have revealed viper toxins also induce neurotoxic effect. While this effect is thought to primarily be driven by prey selectivity, no study has quantified the taxonomically specific neurotoxicity of the viper clade consisting of Daboia, Macrovipera, Montivipera, and Vipera genera. Here, we teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…While 3FTx has been shown in very small quantities within the venom proteome of M. mexicanus , the levels present are far too low to explain the level of activity observed in this study. As post-synaptic PLA 2 have previously been isolated from Bitis venoms [ 58 ] and post-synaptic neurotoxicity is broadly present within that genus [ 2 ], as well as other viperine genera [ 4 ], it is hypothesised that similar PLA 2 are responsible for the alpha-1 orthosteric site binding activity in pit vipers such as the species in this study. This may also be the case for the aforementioned activity in other pit vipers, such as the American Bothriechis [ 3 ] and the Asian Calloselasma [ 5 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While 3FTx has been shown in very small quantities within the venom proteome of M. mexicanus , the levels present are far too low to explain the level of activity observed in this study. As post-synaptic PLA 2 have previously been isolated from Bitis venoms [ 58 ] and post-synaptic neurotoxicity is broadly present within that genus [ 2 ], as well as other viperine genera [ 4 ], it is hypothesised that similar PLA 2 are responsible for the alpha-1 orthosteric site binding activity in pit vipers such as the species in this study. This may also be the case for the aforementioned activity in other pit vipers, such as the American Bothriechis [ 3 ] and the Asian Calloselasma [ 5 ].…”
Section: Discussionmentioning
confidence: 92%
“…Snake toxins targeting the α-1 nAChR have evolved independently on three separate occasions: 3FTx (three-finger toxins) which are abundant in many elapid and colubrid snake venoms [ 6 , 7 , 8 , 9 ]; phospholipase A 2 (PLA 2 ) toxins such as those from Bitis [ 10 , 11 , 12 ]; de novo evolution of neurotoxic peptides within the propeptide region of the gene encoding for natriuretic peptides, which are present in linear forms, including azemiopsins from Azemiops [ 10 ] and waglerins from Tropidolaemus venoms [ 12 , 13 ]. While these toxins are responsible for lethal effects in some venoms, as seen in elapid snakes, they may be highly specific for non-mammalian lineages [ 4 , 7 , 8 , 14 ]. Consequently, as many snake venom effects are known only from clinical reports, the non-mammalian selective neurotoxic activity may not be noted in case studies.…”
Section: Introductionmentioning
confidence: 99%
“…No further symptoms were described after two ampules of antivenom (European viper venom antiserum, 'Zagreb'). The bites of V. berus have a broad spectrum of potential effect, and is often per se defined as cyto-and hemotoxic with pro-or anticoagulant inducing effects and blood factor X activators 92,100 .However, one problem is that the neurotoxic effects of V. berus envenoming are poorly documented in comparison to the amount of bite cases, but known for the other two medical relevant species, V. aspis and V. ammodytes 24,[101][102][103][104][105] . PLA2, such as presynaptic ammodytoxin isoforms and postsynaptic isoforms of aspin and vipoxin, are most likely responsible for these effects 94,106,107 .…”
Section: Vipera -Eurasian Vipersmentioning
confidence: 99%
“…Viper envenomation are characterized by mostly hemotoxic and tissue damaging clinical effects, while several Viperinae venoms, such as from the Russell's viper Daboia russelii or the nosehorned viper Vipera ammodytes are also known for their capability to cause neurotoxic effects [23][24][25][26] . Responsible for this spectrum of symptoms are more than 50 known toxin families in snake venoms, which are physiologically diverse: they occur in multiple isoforms and are functionally modulated via posttranslational modifications [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Macrovipera schweizeri venom appears to present the lowest factor X activation rates of the Macrovipera taxa examined ( Chowdhury et al, 2021a ). Furthermore, the taxon-specific neurotoxicity of various Palearctic vipers showed that, while the M. lebetinus subspecies M. l. cernovi , M. l. obtusa and M. l. turanica present a strong affinity for amphibian mimotopes, the venom of M. schweizeri targets more effectively lizard mimotopes ( Chowdhury et al, 2022 ). Taken together, these results suggest the presence of interspecific venom variation within the genus Macrovipera .…”
Section: Introductionmentioning
confidence: 99%